Analysis of Islamic Religious Education in Responding to the Challenges of Globalization - Jamil, Alfan (Universitas Nurul Jadid, 2023)
Globalization brings significant changes in various aspects of life, including education. In schools, Islamic Religious Education faces substantial challenges in the face of current globalization, which often affects local cultural values and identity. This journal aims to analyze how Islamic Religious Education can adapt and respond to the challenges of globalization in schools. This research uses a qualitative approach with literature study methods and in-depth interviews with educators and educational practitioners. The results of the analysis show that P.A.I. in schools needs to integrate global values while maintaining the basic principles of Islamic teachings. The proposed strategy includes adjusting the curriculum to include international issues with an Islamic perspective, training educators to face global challenges, and developing relevant learning media. It is hoped that these findings can guide the development of educational policies and practices that are more responsive to the challenges of globalization while still maintaining the integrity of Islamic values.